Nitrogen photofixation ability of g-C3N4 nanosheets/Bi2MoO6 heterojunction photocatalyst under visible-light illumination - Vesali-Kermani, Elham; Habibi-Yangjeh, Aziz; Diarmand-Khalilabad, Hadi; Ghosh, Srabanti (Journal of colloid and interface science, 2020)
[Display omitted] •g-C3N4 nanosheets/Bi2MoO6 photocatalysts as efficient photocatalysts are reported.•The nanocomposite with 30% of Bi2MoO6 displayed the highest activity in ammonia production.•Activity was 1.9 and 9.2 times higher than g-C3N4 nanosheets and Bi2MoO6, respectively.•Effects of solvent, pH, and electron scavenger on the rate of ammonia production were studied. In this study, we combined bismuth molybdate with graphitic carbon nitride nanosheets with different percentages of 10%, 20%, 30%, and 40%, in which noticeable N2 photoreduction under visible-light illumination was seen for the binary g-C3N4 nanosheets/Bi2MoO6 photocatalysts, denoted as NCN/BMO. The XPS, HRTEM, TEM, XRD, EDX, UV–vis DRS, N2 adsorption-desorption, FT-IR, TGA, PL, photocurrent, and EIS instruments were utilized to characterize the fabricated photocatalysts. The results displayed the construction of type-II heterojunction between the NCN and BMO components for the easy charge transfer. Under mild conditions and using ethanol as a hole scavenger, the NCN/BMO (30%) nanocomposite showed the maximum capability for ammonia generation by 3271 µmol/L g, which is 1.9 and 9.2 times higher than the NCN and BMO components, respectively. The effects of solvent type, pH of solution, and electron scavenger on the rate of NH4+ production were also studied and conversed. Finally, the stability of the NCN/BMO (30%) nanocomposite was evaluated for four cycles, in which the results were desirable.